2009
DOI: 10.1590/s0102-86502009000600003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental splenectomies and malaria in mice

Abstract: Purpose:To evaluate the importance of spleen in malaric infection in murino model, comparing the parasitemia and the titles of imunoglobulins in the different groups. Methods: It was used female mice non-isogenic, in inoculated with Plasmodium berghei, cepa ANKA, intraperitoneally. The parasitemia was analyzed in 23rd, 25th, 27th and 32nd day of the experiment, being the stained blood' exam colored by Giemsa. The titles of the total serum immunoglobulins IgM and IgG were analyzed by Dot-ELISA technique, at 6th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Furthermore, glial cells increase neutrophil survival and phagocytosis, which could provide protection against brain infection [ 34 ]. Since cell-based therapy decreases parasite load in noncerebral malaria models [ 12 , 13 ], we hypothesized that BM-MSC administration would stimulate phagocytosis and promote parasite clearance, which has been extensively described in the literature as occurring in the spleen [ 35 , 36 ]. The spleen is well characterized as a hematopoietic site during experimental malaria [ 37 ]; the increased numbers of constitutive hematopoietic stem progenitor cells observed in the spleen during P. berghei infection impair parasitemia exacerbation and increase mouse survival [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glial cells increase neutrophil survival and phagocytosis, which could provide protection against brain infection [ 34 ]. Since cell-based therapy decreases parasite load in noncerebral malaria models [ 12 , 13 ], we hypothesized that BM-MSC administration would stimulate phagocytosis and promote parasite clearance, which has been extensively described in the literature as occurring in the spleen [ 35 , 36 ]. The spleen is well characterized as a hematopoietic site during experimental malaria [ 37 ]; the increased numbers of constitutive hematopoietic stem progenitor cells observed in the spleen during P. berghei infection impair parasitemia exacerbation and increase mouse survival [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using P. berghei -infected mice, found that animals with full splenectomies had parasitemias double those found in intact and partially splenectomized mice [31]. Additionally, when Moore et al [32] assessed parasite clearance in DHA-treated intact and asplenic mice, it was found that the capacity to clear parasites was reduced in the asplenic population.…”
Section: Discussionmentioning
confidence: 99%
“…Splenic clearance of parasitized RBCs was determined to play an important role in both humans (17) and mice (27). In this study, we identified Plasmodium yoelii as the most relevant rodent model to study in vivo splenic RBC clearance, for it shares similar invasion characteristics (28) with Plasmodium falciparum.…”
mentioning
confidence: 99%